Dimensi Konflik Sosial Pemerintahan Husni Mubarok dalam Novel Ṡauratu al-‘Arāyā (Telaah Sosiologi Sastra) - M Syaiful Kamal (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2018)
Ṡauratu al-'Arāyā is created by Maḥmūd Ahmad 'Ali an Modern Arabian writer of Egypt. The novel which lift the revolution that occurred in Egypt. The study of this novel is to reveal various things regarding the Egyptian revolution of 2011.This novel is analyzed using the sociological theory of literature. Literary sociology research emphasizes the importance of the relationship between literary work and society. This principle is based on the assumption that literary work is not present, it is created in a situation of social and cultural emptiness. On the one hand, community life can inspire writers to produce literary works. On the other hand, literary works can display a picture of people's live.The result of this analysis is the Egyptian revolution of 2011 is occurred and motivated by two main aspects, namely aspects economic, social, and politic aspects. The economic aspects include poverty, unemployment, and housing. Social aspects include corruption, arbitrariness of officials, weddings, and social status. Revolution is centered in the middle of the capital city and scattered in various areas in Egypt followed by a variety of groups their is unemployment, homeless, youth, sickness, official employee, museum official, government official, orphan, man of letters, and servant. The Egyptian Revolution in 2011 has not given a direct impact on the claims made.Keyword: Ṡauratu al-'Arāyā, Egyptian revolution, sociology.AbstrakNovel Ṡauratu al-'Arāyā dikarang oleh Maḥmūd Ahmad 'Ali seorang penulis Arab modern di Mesir. Novel ini mengangkat tema revolusi yang terjadi di Mesir. Studi tentang novel ini adalah untuk mengungkapkan berbagai hal mengenai revolusi Mesir 2011. Novel ini dianalisis menggunakan teori sastra sosiologis. Penelitian sosiologi sastra menekankan pentingnya hubungan antara karya sastra dan masyarakat. Prinsip ini didasarkan pada asumsi bahwa karya sastra tidak ada, itu diciptakan dalam situasi kekosongan sosial dan budaya. Di satu sisi, kehidupan komunitas dapat menginspirasi penulis untuk menghasilkan karya sastra. Di sisi lain, karya sastra dapat menampilkan gambar kehidupan masyarakat. Hasil dari analisis ini adalah revolusi Mesir tahun 2011 terjadi akibat dimotivasi oleh tiga aspek utama, yaitu aspek ekonomi, sosial, dan aspek politik. Aspek ekonomi termasuk kemiskinan, pengangguran, dan perumahan. Aspek sosial termasuk korupsi, kesewenang-wenangan pejabat, pernikahan, dan status sosial. Revolusi berpusat di tengah ibu kota dan tersebar di berbagai daerah di Mesir dengan diikuti berbagai kelompok yang terdiri dari para pengangguran, tunawisma, pemuda, orang-orang sakit dan paramedis, karyawan perusahaan, pegawai cagar budaya, pegawai pemerintah, anak yatim, komunitas sastrawan, dan budak (ḥimār). Revolusi Mesir 2011 belum memberikan dampak secara langsung terhadap tuntutan yang disampaikan.